Does a single high dose of vitamin D3 have an effect on fracture healing? Animal study - Zakir Hussain, Ahammed; Jambu, N.; Lourdes, Kevin (International Journal of Research in Orthopaedics, 2016)
Background: Vitamin D has an important role in the regulation of calcium by stimulating intestinal absorption of calcium and phosphorous and osteoclastic resorption of bone thus being critical building bone. Given the high prevalence, severity, and cost of osteoporotic fractures, prevention strategies that are effective, low in cost and well tolerated are needed. One promising prevention strategy may be vitamin D supplementation. This animal study was done in order to establish the role of Vitamin D in fracture healing among rabbits. Methods: 8 rabbits were involved in the study with 4 in the control group & 4 in the test group. A fracture was surgically induced on both the groups following which a single high dose of vitamin D was administered intra muscular injection to the test group and normal saline for the control group. Biomechanical properties of the fractured bones such as energy absorbed until fracture (EAUF), maximum load (N) and diameter at the fracture site (D) were assessed 12 weeks later. Results: Mean value of EAUF for test group was 401.8 N-mm and control group was 404 N-mm. Mean value of maximum load in control group is 228.8 N and for test group is 186.9 N. Conclusions:From the above results, the authors did not find any significant improvement in fracture healing in test group. Hence, further investigations are to be needed to prove the role of vitamin D3 in fracture healing.